IMPLEMENTASI SISTEM KENDALI PID PADA VIVARIUM BIOAKTIF BERBASIS IOT - Bamaramzy Rakan Faishal; Henni Endah Wahanani; Retno Mumpuni (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
This study aims to implement an Internet of Things (IoT)-based Proportional–Integral–Derivative (PID) control system for a bioactive vivarium using the ESP32 microcontroller to automate microclimate regulation. The system was developed using the Rapid Application Development (RAD) framework by integrating temperature, air humidity, and soil moisture sensors with a multi-actuator control system. PID parameters were determined through manual tuning to achieve a stable, fast response with minimal overshoot. System performance was evaluated over a ten-day testing period to assess its ability to maintain environmental conditions at predefined setpoints. The results demonstrate that the proposed system successfully maintained stable temperature, air humidity, and soil moisture within the desired thresholds. The PID feedback mechanism effectively minimized microclimate fluctuations, supported the sustainability of the vivarium ecosystem, and improved environmental control efficiency. Furthermore, integration with the Blynk platform enabled reliable real-time remote telemetry monitoring, facilitating continuous system supervision and informed decision-making by users.